2008
DOI: 10.1186/1477-3155-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of CdSe Nanoparticles in Caco-2 Cell Cultures

Abstract: BackgroundPotential routes of nanomaterial exposure include inhalation, dermal contact, and ingestion. Toxicology of inhalation of ultra-fine particles has been extensively studied; however, risks of nanomaterial exposure via ingestion are currently almost unknown. Using enterocyte-like Caco-2 cells as a small intestine epithelial model, the possible toxicity of CdSe quantum dot (QD) exposure via ingestion was investigated. Effect of simulated gastric fluid treatment on CdSe QD cytotoxicity was also studied.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 40 publications
(53 reference statements)
3
97
0
1
Order By: Relevance
“…The exposure of CdSe quantum dot on enterocytelike Caco-2 cells as a model for intestine epithelium was investigated. Results suggested that acid treatment of PEGcoated quantum dots increased the toxicity [130]. Another study investigated the in vitro and in vivo toxicity of CdTe nanoparticles on human hepatoma HepG2 cells [131].…”
Section: Effects On Cell Linesmentioning
confidence: 99%
“…The exposure of CdSe quantum dot on enterocytelike Caco-2 cells as a model for intestine epithelium was investigated. Results suggested that acid treatment of PEGcoated quantum dots increased the toxicity [130]. Another study investigated the in vitro and in vivo toxicity of CdTe nanoparticles on human hepatoma HepG2 cells [131].…”
Section: Effects On Cell Linesmentioning
confidence: 99%
“…11 Once the free iron enters the cytosol, it is able to interact with hydrogen peroxide physiologically formed by different types of enzyme-catalyzed reactions, generating free radicals. 12,13 In general, the cellular oxidative stress caused by the formation of ROS is considered to be a key mechanism of nanomaterial toxicity. 2,10,[14][15][16][17][18][19] Moreover, oxidative stress, together with its secondary consequences, is known to be involved in the pathogenesis of many diseases, such as cancer, diabetes, and respiratory problems, as well as in aging processes.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, 10 mL of QDs in CHCl 3 were placed in an eppendorf tube and after total evaporation of CHCl 3 , 10 mL of HClO 4 1 M was dropped for the dissolution of the QDs. Previously, it has been reported in the literature that a concentrated acid is able to etch and dissolve Cd-based quantum dots [24,25]. Therefore, we could assume that the attack of CdSe QDs with concentrated acid is likely to follow a similar reaction to macroscopic CdSe (Eq.…”
Section: Cdse Qds In Organic Mediummentioning
confidence: 99%